Acute Kidney Injury in Cirrhosis of Liver: it’s Clinical Spectrum and Association of Various Clinical Outcomes with Advancing Cirrhosis of the Liver - Iftikhar Haider Naqvi, Muhamad Salman, Muhammad Tanveer Alam, Muhamad Ubaid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background & Objectives: Pakistan in tandem marks mortality of advance cirrhosis due to complications like hepatic encephalopathy, upper gastrointestinal bleeding and Acute kidney injury (AKI) contributing further morbidity and mortality. The study aimed to determine frequency, types and severity of AKI among cirrhotics and find association between AKI with various clinical outcomes among advance cirrhotics. Methods: All cirrhotics (both genders), age > 18 years of various aetiologies with confirmed AKI were included and analysed retrospectively. Clinical, antiviral treatment and biochemical predictors of mortality in AKI were analysed by univariate regression however independent risk factors were analysed by multi regression (significant P values < 0.05). Results: Out of 271 cirrhotics, 188 (69.37%) had AKI. Commonest to least common AKI pattern was pre-renal (59.5%), intrinsic (37.7%) post-renal (2.1%). Majority (45.2%) had international club of ascites (ICA-AKI) stage 3, (33.5%) ICA-AKI stage 2 and (21.3%) ICA-AKI stage 1. The overall mortality with AKI at 1,6 and 12 months were 12.8%, 39.1% and 54.3% respectively (significant p 0.001). Increased creatinine, international normalized ratio (INR), bilirubin, albumin, Child Turcotte Pugh (CTP) and Model of end stage liver disease (MELD) were in-hospital predictors of mortality where INR and albumin proved significant. Conclusion: AKI being frequent challenge among cirrhotics has commonest pattern as pre-renal with majority having severe AKI, ICA-Stage 3. Patients with AKI had higher mortality versus non-AKI. Rising creatinine, serum bilirubin, severity of cirrhosis (CTP and MELD score) were the significant predictors of in-hospital mortality where INR and albumin were most significant. Keywords: Acute kidney injury, international club of ascites, cirrhosis of liver, child Turcotte Pugh, International normalized ratio